THE IMPACT OF RISK AND PROFITABILITY ON INVESTMENT BANKING MANAGEMENTM BRIEFCASE - SENIV, Bohdan; KOROL, Volodymyr (Herald of Khmelnytskyi National University. Economic sciences, 2023)
Deeply penetrating all spheres of the economy, banking institutions exert an active influence on economic growth and social development of the country. The intensity of investment processes, the dynamics of the development of production of goods and the provision of services largely depend on the ability of banks to rationally manage risks.If in economically developed countries the theory and practice of the investment business of banks is well developed, then in relation to the conditions of the domestic economy, it undergoes a process of adaptation, which is caused by a number of characteristic differences. In particular, there are: unstable economic and political situations in the country; critical financial condition of a significant number of industrial enterprises; danger of significant inflationary processes; imperfection of the legal framework; lack of developed stock market infrastructure. Banking difficulties can be overcome only based on a systematic approach to bank management in general and risk management in particular.The theoretical and methodological foundations of risk management in banking are considered. The role of investment risks in the general system of banking risks is determined. The essence of the bank's investment portfolio and the impact of risks on it are characterized. An assessment of the risks of the implementation of the investment project was carried out. The influence of risk and profitability on the management of bank portfolio investment is determined. The directions for improving the management of the bank's investment portfolio, taking into account risk, are substantiated.
Keywords: investment banking portfolio; investment risk; investment project; diversification; premium; systematic and unsystematic risks